Trade, Labor Markets, and the China Shock: What Can Be Learned from the German Experience? - Christian Dustmann (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
A number of recent works have shown that the substantial increase in imports to the United States from China over recent decades led to large but highly concentrated negative labor market outcomes for those workers most exposed to these imports. On the other hand, such substantially negative effects were largely absent in Germany, the world's fourth-largest economy. This paper discusses aspects that likely contribute to explaining these differences: the German industry structure, its nature of industrial relations, as well as the ability to and willingness of workers to retrain. Moreover, with the China shock being in large part over, any future shocks will most likely look quite different. It is unlikely that the economic shocks of the future will affect the same workers, in the same ways, as the China shock did. Therefore, by focusing the policy discussion on trade policy exclusively, we may overlook other looming challenges. Instead, it may be more fruitful to discuss how to design industrial policies, labor market policies, and education and training policies so that modern economies can adapt flexibly to a range of possible shocks.
Keywords: F14; F16; F66; 330; Trade; Inequality; Germany; Industrial Relations; Vocational Training